IMPROVING THE METHODOLOGY OF INCREASING THE EFFICIENCY OF ECONOMIC GROWTH IN INDUSTRIAL ENTERPRISES IN THE REGION - Eshqobilova, Nargiza Mengnarovna (THE INNOVATION ECONOMY, 2026)
This article analyzes the issues of increasing the efficiency of economic growth in regional industrial enterprises. Existing methodologies are studied, their shortcomings are identified, and improved approaches that can be used in modern economic conditions are proposed. Also, a methodological model is developed based on the factors of innovative development, digital transformation, and efficient use of resources.